Detection of outliers in multiple circular regression model - Alkasadi, Najla Ahmed Salem (Institute of Engineering Mathematics, 2018)
Referring to the statement of problems above, the researcher has outlined the objectives of this study as follows; to examine the robustness of the multiple circular regression estimation towards the occurrence of outliers in the data; to propose two new statistics given by DFBETAc and DFFITc statistics to determine outliers observations in MCRM; to extend the use of three statistics which are COVRATIOc, DMCEc and DMCEs statistics to determine outliers observations in MCRM; to compare all the proposed statistics in (ii) and (iii), and illustrate all the proposed statistics on real life data.